Relations of carbon isotope discrimination and other physiological traits to yield in common bean (Phaseolus vulgaris) under rainfed conditions - White, Jeffrey W.; Castillo Franco, J.A.; Ehleringer, JR; García, J.A.; Singh, Shree P. (Cambridge University Press, 1994)
Although direct selection for seed yield under water deficit can result in genetic gains in the common bean (Phaseolus vulgaris L.), progress could be enhanced through selection for additional traits that are related to underlying mechanisms of adaptation to water deficit. Carbon isotope discrimination (?) has received considerable attention as an indicator of water use efficiency and adaptation to water deficit. To test the utility of ? as a selection criterion, ? and other traits were measured in F2 and F3 generations of a nine-parent diallel grown under rainfed conditions at two locations in Colombia with contrasting soil types. An irrigated trial was also conducted at one location. Significant (P 0·05) differences among parents, F2 and F3 were found for carbon isotope discrimination (?), leaf optical density (OD), leaf nitrogen (N) and potassium (K) concentrations, relative duration of pod-filling period (RDPF), shoot dry weight (SDW) and harvest index (HI). Effect of location and water regime and their interactions with genotype were also frequently significant. Heritability estimates, determined by regressing the F3 on the F2, ranged from 0·11±011 (S.E.) to 0·33 ±0·10 for OD, 0·22 ± 0·07 to 0·44±0·09 for N, 0·04±0·05 to 0·29±0·08 for K, 0·40 ± 0·08 to 0·43 ± 0·15 for RDPF and 0·30±0·22 to 1·00±0·24 for SDW. All values for ? and HI did not differ significantly from zero. Correlations between seed yield and OD and RDPF were negative, whereas those with N, K, SDW, and HI were positive. For all traits, mean square values for general combining ability (GCA) were usuall significant and larger than those for specific combining ability (SCA). All significant GCA effects for ? for Rio Tibagi , San Cristobal 83 and Apetito were negative, while those for Bayo Rio Grande , Bayo Criollo del Llano , Durango 222 and BAT1224 were positive. Although ?appears unsuitable as an indirect criterion for selection for yield under water deficit, further study of genotypes exhibiting contrasting values of A might reveal differences in mechanisms of adaptation to water deficits, thus leading to other selection criteria or identification of valuable parental lines.